Factores de manejo que influyen en la presentación de conductas agresivas en perros - Núñez, Fernando; Cornejo, Javiera; Morales, María A. (Avances en Ciencias Veterinarias, 2006)
Dog aggression is the behaviour problem that presents more risks for humans and other animals, because of the potential damage that this behaviour can cause. The accidents to aggressive behaviours in dogs, affect millions of people every year. The problem of the aggressiveness in dogs is complex, because this conduct is determined by several different factors. It is described that around 30% of behaviour in dogs, is determined by genetic or intrinsic factors, while the 70% remainder is determined by the environmental factors and conditions that surround the dog.The purpose of the present study is to offer information of different variables that influence the presentation of aggressive behaviours in dogs, so it can be used to generate technical criteria that support an adequate legislation about the control and management of potentially aggressive dogs.The purpose of the present studuy is to offer information of different variables that influence the presentation of aggressive behaviours in dogs, so it can be used to generate technical criteria that support an adequate legislation about the control and management of potentially aggressive dogs.For these purpose opinion polls where applied to: breeders, dog trainers and owners. Eleven breeds were selected: Rottweiler, Pitbull, Akita Inu, Dogo Argentine, Bull Mastiff, Mastin Napolitano, Doberman, Saint Bernard, Great Danish, German Shepard and mixed race dogs.The results show that, for the dogs involved in the study, there is a statistically significant relation between the presentation of aggressive behaviours and the variables breed, sex, relation of the pet with the family group, type of advising received, information of the breed characteristics, place in which the pet was acquired, age of the pet at moment of acquirement, methods utilized to establish the dominance, training and purpose of training. For the breeders of dogs was established that, the parent's selection is mainly based on physical features and pedigree, and in a second place in temperament gestures. In all the breeding places an interview is made to ascertain the living conditions and characteristics of the pet, but if the results are not satisfactory for the breed, only half of the breeders do not sell the dog. Half of the trainers uses physical submission to dominate the dog, and nine of ten polled trainers carry out some training that enhance the protection behaviour and aggressiveness in dogs, these kind of training is most often requested for Rottweiler, Akita Inu, German Shepard.